A double-blind, placebo-controlled, randomised, multicentre, proof-of-concept and dose-finding phase II clinical trial to investigate the safety, tolerability and efficacy of adrecizumab in patients with septic shock and elevated adrenomedullin concentration (AdrenOSS-2). Issue 2 (6th February 2019) - Geven, Christopher; Blet, Alice; Kox, Matthijs; Hartmann, Oliver; Scigalla, Paul; Zimmermann, Jens; Marx, Gernot; Laterre, Pierre-François; Mebazaa, Alexandre; Pickkers, Peter
Abstract : Introduction: Sepsis remains a major health problem with an increasing incidence, high morbidity and high mortality. Apart from treatment with antibiotics and organ support, no approved specific adjunct therapies currently exist. Adrenomedullin (ADM) is a vasoactive peptide. High plasma concentrations of ADM correlate with worse outcome in sepsis patients. Preclinical work with the non-neutralising ADM-binding antibody adrecizumab showed promising effects in animal models of septic shock, including improved vascular barrier function, reduced vasopressor demand and organ dysfunction and increased survival. Therapeutic use of adrecizumab may therefore improve outcome in critically ill patients with septic shock and high ADM plasma concentrations. Phase I studies in healthy volunteers did not reveal any safety concerns. In this biomarker-guided trial, the safety and efficacy of adrecizumab will be investigated in patients with septic shock. Methods and analysis: We describe a phase II, randomised, double-blind, placebo-controlled, biomarker-guided, proof-of-concept and dose-finding clinical trial in patients with early septic shock and high concentration of circulating ADM. A total of 300 patients will be enrolled at approximately 30 sites within the European Union. Patients are randomised to receive active treatment (2 and 4 mg/kg adrecizumab) or placebo, in a 1:1:2 ratio. Patient selection is guided by clinical parameters, and biomarker-guided by measurement of circulating biologically active ADM concentration at admission. Primary endpoint is safety and tolerability of adrecizumab over a 90-day period. A key secondary endpoint is the Sepsis Severity Index over a 14-day period. Ethics and dissemination: This study is approved by relevant institutional review boards/independent ethics committees and is conducted in accordance with the ethical principles of the Declaration of Helsinki, the European Medicines Agency guidelines of Good Clinical Practice and all other applicable regulations. Results of this study will be published in a peer-reviewed scientific journal. Trial registration number: NCT03085758 ; Pre-results.